(untitled) - Tucker, James F. (New York, 1988)
This book assumes that the average advice-seeker can digest readily information the author has learned from years of experience. The author knows, and tells, a lot, not only about advantageous personal money management, but also about the U.S. financial structure and its sophisticated and infinitely varied investment possibilities. Some average wage earners are sure to be discouraged by the sheer mass of material presented, or confused by the multiple financial choices even Wall Street managers have trouble with
Keywords: Finance, personal,Investments